IMPACT OF ONLINE EDUCATION ON ACADEMIC ACHIEVEMENT: A COMPREHENSIVE STUDY - Gowher Hassan (RADJA PUBLIKA, 2023)
The study explores the realm of education by conducting a comprehensive evaluation of the effects of online education on academic achievement. In the digital age, online education has gained prominence as an alternative and supplementary mode of learning. The study aims to critically analyze the impact of online education on students' academic success, encompassing various academic levels and subjects. By examining a range of factors, including learning outcomes, student engagement, and educational equity, the study seeks to contribute to the ongoing discourse on the efficacy and potential drawbacks of online education in fostering academic excellence.